Consumers Preferences, Subsistence and Real Wage - Andrews, D. (Journal of Income Distribution®, 1993)
In classical political economy, the real wage derives its reality from its association with a given set of products that provides for the subsistence of workers through time. In neoclassical theory the connection between the real wage and a given set of products is broken, because the restriction of workers’ consumption to a particular set of products conflicts with the idea of individual consumer preference. Thus, the ‘reality’ of the real wage in neoclassical theory is grounded differently, in a particular standard of value that can be called an index number standard. The difficulties involved with this construction raise questions about the theoretical adequacy of the notion of real wage itself. In particular, this leads to a conclusion that stands in sharp contrast to the empiricist proclamations of neoclassical theory.